Wizja ¡ proroctwo w Liber ostensor Jana z Roquetaìllade (+1365) - Grzeszczak, Jan (Poznańskie Studia Teologiczne, 2009)
The issue touched in the article is vision and prophecy on the basis of Liber ostensor by John of Roquetaillade, a Franciscan visionary and long-term prisoner of Franciscan and Roman Inquisition. This extensive work was written in 1356 in Avignon and was dedicated to the cardinal Elie Talleyrand de Périgord, who, as a nuncio, had to carry into effect the conclusion of peace between England and France. Liber ostensor is a Franciscan and eschatological work. It conveys an apocalyptic augury of events which will take place in the latter part of the XIV century. One of the main plots of the work is a medieval dispute about evangelical poverty. It resulted in the radicalization of views of John of Roquetaillade. The Franciscan experienced many visions of angels, Mother of God, St Francis of Assisi, and also the Antichrist, which strengthened his conviction about the rightness of his views. John of Roquetaillade prophesies a punishment that will affect the Avignonese papacy and Europe. After sins of people of church have been punished, there will appear a pope-reformer, who will lead mankind into a new era, directly preluding the end of the world. The author of Liber ostensor is an interesting example of the resurgence of millenarism in the Middle Ages.